Heteroepitaxial growth of CaGe2 films on high-resistivity Si(111) substrates and its application for germanane synthesizing. (July 2023) - Okada, Kazuya; Shibayama, Shigehisa; Sakashita, Mitsuo; Nakatsuka, Osamu; Kurosawa, Masashi
Abstract: Realizing a germanane (GeH) film on insulating substrates is strongly required to understand its intrinsic electric properties in discussing the potential applications for the next-generation field-effect transistor channels. This study investigates the heteroepitaxial growth of CaGe2 —the precursor of the GeH—films on a high resistive substrate of FZ-Si(111) using a molecular beam epitaxy with the deposition temperature ( T depo ) as a variable. X-ray diffraction and Raman spectroscopy analyses indicated that a metastable polytype of 2H was dominated in the epitaxial CaGe2 films; the T depo must be less than 700 °C to prevent Si diffusion from the substrates. We also synthesize GeH films by immersing some CaGe2 films in HCl acid solutions at a low temperature of −40 °C. Although the obtained grain size of GeH was still as small as several hundred nanometers, we believe that the present study is the first step in obtaining the GeH continuous films directly on insulators necessary for electrical characterizations.